Behaviour of reinforced concrete column under biaxial cyclic loading: state of the art - Rodrigues, H. (2013)
The cyclic behaviour of reinforced concrete columns has been object of many experimental studies in the last years, mostly focused on the unidirectional loading of columns under constant axial load conditions. In this research work, the existing test on reinforced concrete (RC) columns under biaxial load has been reviewed, underlying their main findings. In general, the experimental results show that the RC columns' response is highly dependent on the loading pattern, and the biaxial loading induces a decrease in the maximum strength and anticipates each damage state. Thus, in columns where demands are expected with large moments in both directions, specific detailing should be provided in their critical regions in order to improve the columns' performance and avoid premature failure.